Effects of oxytocin on adreno-medullary catecholamine synthesis, uptake and storage in rats exposed to chronic isolation stress. (2nd April 2016) - Jovanovic, Predrag; Stefanovic, Bojana; Spasojevic, Natasa; Puskas, Nela; Dronjak, Sladjana
ABSTRACT: Purpose/aim: The adreno-medullar system represents one of the main systems involved in the response to stressful events. The neuropeptide oxytocin, is highly sensitive to the social environment, and regulates autonomic function. Adreno-medullary activity is dependent on the synthesis of catecholamine, its reuptake, release, degradation and vesicular transport. A direct influence of oxytocin on catecholamine synthesizing enzyme and transports in animals exposed to chronic social isolation stress has not been studied yet.Materials and methods: In the present study, we examined the effect of chronic oxytocin treatment on the level of plasma catecholamine and its content, mRNA and protein levels of tyrosine hydroxylase (TH), noradrenaline transporter (NET) as well as vesicular monoamine transporter 2 (VMAT2) in the adrenal medulla of socially isolated rats.Results: Our results show that, by the end of 12 weeks, social isolation did not produce any significant changes in catecholamine content but increased plasma catecholamine level and synthesis in the adrenal medulla. Oxytocin treatment had no further effect either on catecholamine synthesis or content in socially stressed animals whereas a significant elevation of plasma norepinephrine and epinephrine were reduced. On the other hand, chronic isolation caused a significant increase in VMAT2 and decrease in NET protein levels. Oxytocin treatment brought about an increase in protein levels of NET and its return to the levels of control group. Besides, it further increases VMAT2 protein levels in the adrenal medulla of individually housed rats.Conclusion: The present results show that peripheral oxytocin treatment enhances catecholamine uptake and storage in the adrenal medulla of chronically isolated animals.